Modelling and Optimizing Teacher’s Innovativeness: An Empirical Study using POP SDM Method on Teachers of State Primary Schools - Elyza Martiarini; Soewarto Hardhienata; Widodo Sunaryo (Journal of Industrial Engineering & Management Research, 2023)
The objective of the research is about finding strategies of teacher’s innovativeness by using POP SDM method where it firstly conducted by qualitative research to explore variables affecting teacher’s innovativeness. The dominant variables are creativity and personality as independent variables, and perceived organizational support (POS) as intervening one. After finding variables and constructing model constellation through theoretical framework and expert judgment, then the model is examined by a quantitative research using path analysis on 155 teachers of state primary schools at South Tangerang. On the basis of hypotheses test, the direct effect of variables upon teacher’s innovativeness is Ŷ= 0,283X1 + 0,235X2 + 0,481X3, the direct effect of independent variables upon intervening is X3 = 0,381 X1 + 0,573 X2. Whereas the indirect effect of creativity upon teacher’s innovativeness through POS is βx1yx3 = 0,183, this value is < 0,283X1 which means POS is not significantly effective as intervening on the effect of creativity upon teacher’s innovativeness through POS. While the indirect effect of personality upon teacher’s innovativeness through POS is βx2yx3 = 0,276 that it is > 0,235X2 which means POS is significantly effective as intervening on the effect of personality upon teacher’s innovativeness through POS. Eventually, Sitorem analysis is conducted to determine teacher’s innovativeness improvement by strengthening weak indicators and maintaining good ones in variables ordering based on the highest coefficient correlation. On the basis of SITOREM result, the indicators prioritized to be improved are sequentially from POS, creativity, and personality